Transient Analysis of Microgrids With Parallel Synchronous Generators and Virtual Synchronous Generators - Shi, Kai; Song, Wentao; Ge, Huilin; Xu, Peifeng; Yang, Yongheng; Blaabjerg, Frede (IEEE transactions on energy conversion, 2020)
In recent years, the increasing penetration of distributed generation in microgrids challenges the control and coordination of energy resources. Especially in microgrids with virtual synchronous generator (VSG)-controlled converters and conventional synchronous generators (SG), the inherent inertia difference (i.e., the VSG and SG) results in a poor transient performance when the VSG and/or loads are cut in/out. Thus, this paper explores the transient performance of microgrids with parallel VSG and SG systems. More importantly, a novel pre-synchronization control method is proposed to eliminate the phase jump while meeting the requirements in case of closures or re-closures of generation units. A small-signal dynamic model is presented, and accordingly, the VSG inertia and its damping can be designed considering the capacity ratio of VSG and SG units. In addition, with the power angle stability analysis, an active power provision strategy is introduced to suppress the transient power oscillation due to the inertia difference. Finally, the feasibility of the proposed methods is verified by simulations on a microgrid consisting of parallel VSG and SG units.